The Implementation of Kurikulum Merdeka in Learning English to Students With Special Needs at SMP Plus Rahmat Kediri - Mulyani R, Esthi; Kurniawan, Erwin Hari; Setyawan, Wawan Herry (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to investigate the implementation of the Kurikulum Merdeka in English language learning for inclusive students. The research method used is descriptive qualitative with observation, interview, and documentation triangulation techniques. The respondents involved in this study were English teachers and inclusion students at SMP Plus Rahmat Kediri, especially seventh-grade students. The research instruments used were observation sheets, interview guidelines, and documentation. The results show that implementing Kurikulum Merdeka in English learning positively impacts inclusive students' ability to understand the subject matter, actively participate in learning activities, and increase learning motivation. In addition, this curriculum also helps teachers design more inclusive learning and provide equal opportunities for all students. This research recommends that schools in Indonesia continuously improve and adapt the Kurikulum Merdeka to support better inclusive Education.